2002
DOI: 10.1177/156482650202300302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Dietary Vitamin C Intake on the Level of Vitamin C in Breastmilk among Nursing Mothers in Baghdad, Iraq

Abstract: The vitamin C content of breastmilk was investigated in a group of nursing mothers attending maternal and child health centers in Baghdad during 1998-2000. Two hundred healthy, nonsmoking, 28- to 38-year-old lactating women were studied. Individual samples of breastmilk were obtained for estimation of vitamin C. Dietary data were collected by using 24-hour food recalls. The mean intake of vitamin C was far below the Food and Agriculture Organization/World Health Organization requirement of 26 +/- 2.13 (SD) mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The composition of breast milk (vitamin C and D levels, contents of milk fatty acids) depends significantly on the mother's diet, which has been confirmed in studies by, among others, Basile et al (2006), Saadi et al (2009), Tawfeek et al (2002. The mother's diet may in turn vary seasonally (Watson and McDonald, 2007).…”
Section: Discussionmentioning
confidence: 75%
“…The composition of breast milk (vitamin C and D levels, contents of milk fatty acids) depends significantly on the mother's diet, which has been confirmed in studies by, among others, Basile et al (2006), Saadi et al (2009), Tawfeek et al (2002. The mother's diet may in turn vary seasonally (Watson and McDonald, 2007).…”
Section: Discussionmentioning
confidence: 75%
“…Hidiroglou et al observed that the concentration of vitamin C in cows' milk decreased with the progress of lactation. Human milk is a richer source of vitamin C than cows' milk and its content also changes with the stage of lactation and is greater in colostrum than in milk …”
Section: Resultsmentioning
confidence: 99%
“…Human milk is a richer source of vitamin C than cows' milk and its content also changes with the stage of lactation and is greater in colostrum than in milk. 49…”
Section: Effect Of Stage Of Lactationmentioning
confidence: 99%
“…The etiologies of vitamin C deficiency include low dietary intakes [ 17 ], increased requirements of vitamin C due to smoking [ 28 ] and lactation [ 29 ], decreased bioavailability of vitamin C resulting from peptic ulcer disease (PUD) [ 30 , 31 ], and convective/diffusive losses during dialysis as in chronic renal failure [ 32 ]. To the authors’ knowledge, no study has investigated the predictors associated with vitamin C deficiency defined by plasma concentrations (i.e., <6 mg/L or 34.1 μ mol/L) [ 33 ] in PHN patients.…”
Section: Introductionmentioning
confidence: 99%